Odor characterization of post-consumer and recycled automotive polypropylene by different sensory evaluation methods and instrumental analysis - Prado, Karen S.; Strangl, Miriam; Pereira, Sérgio R.; Tiboni, Adelchi R.; Ortner, Eva; Spinacé, Márcia A.S.; Büttner, Andrea (Waste Management, 2020)
Despite the growing interest of the automotive industry in using recycled polymers, their undesired odor is limiting their application in vehicles’ interior components. To get deeper insights into its causes, this study aimed at characterizing the odor of post-consumer and recycled automotive polypropylene with different contents of talc and an anti-fogging additive. Samples were evaluated by different sensory methods currently applied by the automotive industry (GMW 3205 and VDA 270), which confirmed, that they are not feasible for reuse in interior automotive applications. As these odor evaluations are usually performed by non-trained panelists and do not allow a detailed description of the samples’ single odor qualities, sensory evaluation according to ISO 13299 was performed by trained panelists. Samples showed medium–high odor intensities rated from 5.1 to 5.6, and a general dislike of the odor with hedonic ratings from 1.8 to 2.6 (scale 0–10). Their odor profiles correlated well with the odorants identified by chemo-analytical characterization using gas chromatography–olfactometry (GC-O) and two-dimensional GC-O coupled with mass spectrometry (2D-GC–MS/O). An array of odorants with benzene and phenolic structures were identified as potential contributors to the samples’ overall smell and are likely to originate from degradation of additives commonly used in automotive components. While the addition of talc or anti-fogging additive did not significantly improve the odor of the samples, the description of the samples’ smell and the identification of odor-active compounds related to it allow the development of avoidance strategies for the manufacturing of neutral smelling products intended for vehicles’ interior applications.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Gas chromatography olfactometry; Mass spectrometry; Odorants; Plastic; Recycling; Talc